Case Report: Endogenous endophthalmitis caused by Listeria monocytogenes infection in patients with end-stage renal disease - Chen, Kaichuan; Lyu, Xiao; Liu, Xin; Bi, Yanlong; Wang, Zhen (Frontiers in Medicine, 2025)
PurposeThis paper reports a rare case of endogenous Listeria monocytogenes endophthalmitis caused by hemodialysis in end-stage renal disease (ESRD).MethodsThe patient was a 70-year-old female. The best-corrected visual acuity (BCVA) was light perception (LP). Endogenous endophthalmitis was diagnosed based on clinical manifestations and auxiliary examinations. Pathogenic microbial metagenomic detection of intraocular aqueous was used to identify Listeria monocytogenes. As multiple investigations showed no source of infection, a standardized treatment plan was proposed.ResultsThe treatment included the local application of antibiotics, glucocorticoids and cycloplegic drugs, vitrectomy, intravitreal injection of vancomycin and ceftazidime, anterior chamber irrigation, and systemic antibiotic treatment after the operation. After treatment, the inflammation subsided, and the BCVA at discharge was hand movement (HM).ConclusionOur study highlights the importance of rapid pathogenic microbial metagenomic detection and timely standardized intervention in the treatment of endogenous endophthalmitis.